2013
DOI: 10.6002/ect.2012.0216
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Kidney Biopsies After Acute Allograft Pyelonephritis

Abstract: Objectives: Scarce data exist regarding the effect of acute graft pyelonephritis on kidney histology after a kidney transplant. This study sought to assess the kidney histology at 1 month, and kidney function at 1 year, after acute graft pyelonephritis in kidney transplant patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
4
2
0
Order By: Relevance
“…9,10 Persistent inflammation after the HAGPN diagnosis was previously reported in 28 patients who had repeat biopsies, and it was associated with poor outcomes 1 year later. 28 Overall, our results and those of previous studies are consistent with the general consensus that any allograft inflammation, irrespective of its cause, is detrimental to the allograft. 29,30 This study is limited by the relatively small number of HAGPN cases, which precluded complete multivariate analysis of all factors associated with HAGPN in single variable analysis.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…9,10 Persistent inflammation after the HAGPN diagnosis was previously reported in 28 patients who had repeat biopsies, and it was associated with poor outcomes 1 year later. 28 Overall, our results and those of previous studies are consistent with the general consensus that any allograft inflammation, irrespective of its cause, is detrimental to the allograft. 29,30 This study is limited by the relatively small number of HAGPN cases, which precluded complete multivariate analysis of all factors associated with HAGPN in single variable analysis.…”
Section: Discussionsupporting
confidence: 92%
“…Some evidence also supports a synergistic effect between bacteriuria and rejection on allograft function 9,10 . Persistent inflammation after the HAGPN diagnosis was previously reported in 28 patients who had repeat biopsies, and it was associated with poor outcomes 1 year later 28 . Overall, our results and those of previous studies are consistent with the general consensus that any allograft inflammation, irrespective of its cause, is detrimental to the allograft 29,30 …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the same line, Cartery and al performed systematic graft biopsies one month after an episode of AGPN and compared them to protocol kidney biopsy at one year that did not present AGPN. The authors observed more frequent tubulitis histologic patterns after AGPN all the more so eGFR did not return to baseline ( 26 ), which makes an echo to our data where AGPN were associated with a lower eGFR without altering significantly eGFR decay. The authors also observed an increased CNI through level in the AGPN group ( 26 ).…”
Section: Discussionsupporting
confidence: 78%
“…The authors observed more frequent tubulitis histologic patterns after AGPN all the more so eGFR did not return to baseline ( 26 ), which makes an echo to our data where AGPN were associated with a lower eGFR without altering significantly eGFR decay. The authors also observed an increased CNI through level in the AGPN group ( 26 ). Altogether, those data argued that recurrent AGPN after kidney transplantation were associated with a poorer graft function but also a poorer patient survival all the more so the first recurrent episode occurred early with in the first six months post-transplant.…”
Section: Discussionsupporting
confidence: 78%